Denudation - Sediment Accumulation Systems: Quantitative Aspects of Terrestrial Sediment Yield and Basin Filling - Gerhard Einsele (Berita Sedimentologi, 1998)
The role of terrestrial sediment supply in basin filling and sequence stratigraphy has been frequently mentioned, but quantitative data have been rarely presented and evaluated.